Start with the second equation, to get X.
-3=7x + 8
-11 = 7x
x = -11/7
Now, plug X into the first equation to solve for Y.
7(-11/7) - y = 12
-11 - y = 12
-11 = 12 + y
-23 = y
Y = -23
X = -11/7
2007-01-30 07:36:07
·
answer #1
·
answered by Steven D 5
·
1⤊
0⤋
7x - y = 12- - - - - -Equation 1
-3 = 7x + 8- - - - -- Equation 2
- - - - - - - -
Solve for x second equation
-3 = 7x + 8
-3 - 8 = 7x + 8 - 8
- 11 = 7x
- 11/7 = 7x/7
- 11/7 = x
The answer is x = - 11/7
Insert the x value into equation 1
- - - - - - - - - - - - - - - - - - - - - -
7x - y = 12
7(- 11/7) - y = 12
- 77/7 - y = 12
- 10 - y = 12
- 10- y + 10 = 12 + 10
- y = 22
-1(- y) = - 1(22)
y = - 22
The answer is y = - 22
Insert the y value into equation 1
- - - - - - - - - - - - - - -- - - - - - -
Check for equation 1
7x - y = 12
7(- 11/7) - (- 22) = 12
- 77/7 + 22 = 12
- 10 + 22 = 12
12 = 12
- - - - - - - - - - - -s-
2007-01-30 16:02:00
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
Let's start with this equation:
-3=7x+8
Subtract 8 from both sides:
7x=-11
Divide 7 from both sides:
x=-11/7
Replace x with -11/7 in the next equation:
7(-11/7)-y=12
-11-y=12
Add 11 from both sides:
-y=23
Divide -1 from both sides:
y=-23
The solution set is (-11/7,-23)
Check:
7(-11/7)-(-23)=12
-11+23=12
12=12
-3=7(-11/7)+8
-3=-11+8
-3=-3
I hope this helps!
2007-01-30 15:45:43
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
7x - y = 12
1. add y to both sides
7x - y + y =12 +y
7x = 12 + y
2. subtract 12 from each side
7x -12 = y
equation 2
-3((7x-12) = 7x +8
-21x + 36 = 7x + 8
add 21 x to both sides
36 = 28x + 8
subtract from both sides
36 - 8 = 28x
28 = 28x
x = 1
therefore 7 -y = 12
add y and subtract 12 from both sides
y = -5
check -3(-5) =7(1) + 8
15 = 15
tada.
2007-01-30 15:39:49
·
answer #4
·
answered by Roger G 2
·
0⤊
1⤋
7x-y=12
-3=7x+8 subtract 8 from each side
-11=7x divide both sides by 7
x=-11/7
substitute -11/7 for x
7(-11/7)-y=12
-11-y=12 add 11 to each side
-y=23 multiply both sides by -1
y=-23
(-11/7, -23)
2007-01-30 15:38:42
·
answer #5
·
answered by yupchagee 7
·
1⤊
0⤋
x= (-11/7) y= -23
7x=-11 x= (-11/7)
(-11/7)*7-y=12 -11-y=12 y=-23
2007-01-30 15:40:48
·
answer #6
·
answered by luckylilfukr 3
·
1⤊
0⤋